Afasia expresiva - Caceres Velasquez, Artidoro (1973)
The expresive aphasia is a disorder of the speech in its expresive, predominant, or exclusive (less frequent) aspect. Its neurological study first, specially anatomic-clinical,and then psychological has progressed with the application f the neuropsychology and neurolinguistic, so, it has became of a great importance to the speech pathology which has used specific techniques of analysis to direct its helpful and investigable vector toward a therapeutic. The result of an neuropsycholinguistic analysis of 105 patients, whon 30 were treated since his oral expression, is presented. Statistics relations among the different systems of comunication is stablished and the expresive aphasia is considered as a neuropsycholinguistic Syndrome in the disintegrative nosography of the speech.